JigCell Run Manager (JC-RM): a tool for managing large sets of biochemical model parametrizations. Issue 1 (December 2015) - Palmisano, Alida; Hoops, Stefan; Watson, Layne; Jones, Thomas; Tyson, John; Shaffer, Clifford
Abstract Background Most biomolecular reaction modeling tools allow users to build models with a single list of parameter values. However, a common scenario involves different parameterizations of the model to account for the results of related experiments, for example, to define the phenotypes for a variety of mutations (gene knockout, over expression, etc.) of a specific biochemical network. This scenario is not well supported by existing model editors, forcing the user to manually generate, store, and maintain many variations of the same model. Results We developed an extension to our modeling editor called the JigCell Run Manager (JC-RM ).JC-RM allows the modeler to define a hierarchy of parameter values, simulations, and plot settings, and to save them together with the initial model.JC-RM supports generation of simulation plots, as well as export to COPASI and SBML (L3V1) for further analysis. Conclusions Developing a model with its initial list of parameter values is just the first step in modeling a biological system. Models are often parameterized in many different ways to account for mutations of the organism and/or for sets of related experiments performed on the organism.JC-RM offers two critical features: it supports the everyday management of a large model, complete with its parameterizations, and it facilitates sharing this information before and after publication.JC-RM allows the modeler to define a hierarchy of parameter values, simulation, and plot settings, and to maintain a relationship between this hierarchy and the initial model.JC-RM is implemented in Java and uses the COPASI API.JC-RM runs on all major operating systems, with minimal system requirements. Installers, source code, user manual, and examples can be found at the COPASI website (http://www.copasi.org/Projects ).